Young Afghans facing return - Williams, L; Robinson, K (Refugee Studies Centre, University of Oxford, 2015)
A project in the UK aiming to prepare young men for return to Afghanistan through an assisted voluntary return programme was unsuccessful. A different, longer-term approach might have been more appropriate and more effective